Contrastive analysis of cross-language colloquial correspondence in English and Uzbek Languages - Sotvoldieva Istorakhon Lutfullo Kizi (Zien Journals, 2024)
This article deals with the problem of the classification colloquial units into semantic categories in English, and define their equivalents in Uzbek language, as well as determine common or specific features of the contrasted languages, and explain the discrepancies in translation between two languages.
Keywords: a colloquial word; a colloquial correspondence